Proceso de atención de enfermería en paciente diabético con necrosis en herida quirúrgica por amputación: un estudio de caso - Pinto Rivera, Juliana Jazmín (2024)
Necrosis due to surgical wounds is defined as the death of cutaneous and subcutaneous tissue due to poor blood supply in parts affected by wounds or lacerations. There are several probable causes, but for this particular case that deals with a diabetic patient with necrosis in the surgical incision due to amputation of the right lower extremity, they were due to infections caused by poor care and extreme pressures constantly exerted on tissue located in the wound by wheelchair mobility. This condition can result in poor healing and, in some cases, requires additional treatments such as debridement or surgery to remove necrotic tissue. It is essential to monitor the wounds and consult a doctor if there are signs of necrosis, especially in patients with diseases such as type II diabetes mellitus, since one of its main symptoms is loss of sensitivity in the lower extremities. This case study focuses on the development of an individualized care plan for said patient with the goal of restoring the patient's comfort level through pain management and contributing to full recovery from their surgical incision. The process of obtaining results was carried out through assessment of functional patterns, a tool proposed by the theorist Marjory Gordon, identifying alterations in the aspects of perceptual- cognitive and activity-exercise, in addition, through NANDA, NIC and NOC taxonomies, they were structured. the activities for the care plan, which were focused on pain management, recovery of tissue integrity, and management of impaired physical mobility. In conclusion to this case study, a successful approach to activities carried out within the established times is evident, denoting great effectiveness and allowing the use of said care plan to be recommended in any patient with a similar pathology, ensuring a favorable recovery.